Perbandingan Kinerja Keuangan Bank Umum Syariah Di Indonesia Dengan Metode Sharia Conformity And Profitability - Fajriah, Siti Fajriah Nurazizah; Rahmawati, Rafika (LPPM Universitas Islam 45, 2025)
This research aims to analyze and compare the financial performance of Islamic commercial banks in Indonesia using the Sharia Conformity and Profitability method. Sharia Conformity refers to the extent to which a sharia bank complies with sharia principles in its operations and products. Meanwhile, Profitability assesses the extent to which the bank can generate profits from its business activities. This study uses financial performance data from Sharia Commercial Banks registered with the Financial Services Authority (OJK) for the period 2023. The Sharia Conformity method is measured through analysis of compliance with sharia principles, including product structure, transactions, and compliance with the fatwa of the National Sharia Council (DSN). Meanwhile, Profitability is measured by financial indicators such as Return on Assets (ROA) and Return on Equity (ROE). The results of this research show that using the Sharia Conformity and Profitability (SCnP) method in Sharia Commercial Banks in Indonesia in 2023, namely Bank Muamlamat Indonesia in the URQ position where Bank Muamalat Indonesia has a Sharia Conformity performance of 75% and Profitability of 1.37%, and Bank Aceh Syariah is located in the URQ position where Bank Aceh Syariah has a Sharia Conformity performance of 79% and Profitability of 67.15%. In terms of Sharia Conformity, Bank Aceh Syariah is superior because in 2023 it will achieve good financial performance and growth. This growth is the result of Bank Aceh Syariah's strategy which focuses on performance both in terms of financing and income. Then in terms of Profit it is also superior because Bank Aceh Syariah's performance was recorded to be very encouraging at 67.15% compared to Bank Muamalat Indonesia.